PENGARUH LIKUIDITAS, PROFITABILITAS, AGRESIVITAS PAJAK, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN TRANSPARANSI SEBAGAI PEMODERASI - Meiliana Jaunanda; Jonathan Kevin (Faculty of Economics and Business Universitas Pelita Harapan, 2023)
This study discusses the effect of Financial Ratios and Tax Aggressiveness on Firm Value with Transparency as moderator. The financial ratios used in the study include Current Ratio, Return On Assets, and Debt to Equity Ratio. Firm value is proxied by Price to Book Value (PBV), and the moderating variable, namely Transparency, is proxied by Voluntary Disclosure. This research uses mining companies listed on the IDX during the 2018-2021 period and data obtained from S&P Capital IQ, website BEI, and Stockbit. There are 40 companies sampled in the study. The results obtained are (a) CR and DER have a negative effect on PBV, (b) ROA and ETR have a positive effect on PBV, (c) VD can moderate the relationship between DER and PBV, (d) VD cannot moderate the relationship between ROA, CR, ETR and PBV